2014
DOI: 10.5620/eht.2014.29.e2014004
|View full text |Cite
|
Sign up to set email alerts
|

Skin corrosion and irritation test of sunscreen nanoparticles using reconstructed 3D human skin model

Abstract: ObjectivesEffects of nanoparticles including zinc oxide nanoparticles, titanium oxide nanoparticles, and their mixtures on skin corrosion and irritation were investigated by using in vitro 3D human skin models (KeraSkinTM) and the results were compared to those of an in vivo animal test.MethodsSkin models were incubated with nanoparticles for a definite time period and cell viability was measured by the 3-(4, 5-dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide method. Skin corrosion and irritation were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…KeraSkin™ has also been compared with an in vivo model following treatment with ZnO NPs where skin erosion and irritation were assessed by changes in cell viability. This study demonstrated that the in vitro data were comparable to the in vivo response with the reconstructed skin model (68). …”
Section: D Reconstructed Tissue Modelssupporting
confidence: 62%
“…KeraSkin™ has also been compared with an in vivo model following treatment with ZnO NPs where skin erosion and irritation were assessed by changes in cell viability. This study demonstrated that the in vitro data were comparable to the in vivo response with the reconstructed skin model (68). …”
Section: D Reconstructed Tissue Modelssupporting
confidence: 62%
“…23 Accordingly, irritant treatments, either with SDS or SDBS, significantly increase IL-1α release, in line with literature data. [23][24][25][26][27] More importantly, FLG-SDS and FLG-SDBS induced a significant release of IL-1α, at levels comparable to those released by the relevant positive controls. This observation strengthens the conclusion that these materials can be considered as skin irritants and further supports the hypothesis that, for these materials, skin irritation may be due to the surfactant residues.…”
Section: Papermentioning
confidence: 82%
“…The information available on whether or not metal nanoparticles are dermal irritants is limited. Nanosized cerium dioxide (particle size of 9 nm), silica (7 and 10-20 nm), titanium dioxide (21 nm) and zinc oxide (35 nm) were not irritants in vitro to a human skin equivalent model derived from keratinocytes 14,15,16 . In addition, there is no current evidence that metal nanoparticles are human dermal irritants.…”
Section: Introductionmentioning
confidence: 95%